Polyethylenimine-capped gold nanoparticles in nucleic acid delivery - Hınık, Aykut. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2023., 2023)
RNA interference is a gene editing tool applicable in cancer therapy. Nucleic acid delivery into the cells is challenging due to nucleic acid instability, insufficient cellu lar uptake, and endosomal entrapment. Polyethylenimine (PEI) is a positively charged polymer molecule widely used in nucleic acid delivery. PEI ensures increased endoso mal escape thanks to the proton sponge effect. However, PEI is known to be highly toxic because of molecular size and electrical charge. Gold nanoparticles (AuNPs) are attractive inorganic carriers with biocompatibility, easy synthesis, and adaptability of surface chemistry. In this study, it was aimed to synthesize polyethylenimine-capped gold nanoparticles (AuPEI-NPs) to investigate their cytotoxicity and nucleic acid de livery in breast cancer cells compared to free PEI. Resazurin assay demonstrated that AuPEI-NPs induced less cytotoxicity than free PEI until the 20 µg/ml concentration in breast cancer cells. Flow cytometry demonstrated that AuPEI-NPs yielded signif icantly higher cellular uptake of fluorescently tagged siRNA than PEI. In conclusion, this study demonstrated that AuPEI-NPs are promising nucleic acid carriers in gene therapy with a less cytotoxicity and better cellular uptake than free PEI in breast cancer cells.
Keywords: RNA -- Biotechnology.; Nucleic acids.